2004
DOI: 10.1002/pmic.200300647
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of lung biopsies: Differential protein expression profile between peritumoral and tumoral tissue

Abstract: The cellular proteome shows a dynamic profile and is subjected to changes in response to various stimuli and disease progression. Lung cancer remains the leading cause of cancer death in industrialized countries. In an attempt to find new disease markers, patients suffering from lung carcinoma have been selected to achieve differential protein expression patterns between normal and neoplasic tissue. After two-dimensional electrophoresis, the spots of interest were digested and identified by matrix-assisted las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…At the protein level, consistent with mRNA expression, MG132 , Immenschuh et al 2002, Wijayanti et al 2008, indicating the expression of PRDX1 is inducible by various stimuli. PRDX1 expression is also elevated in most cancers, although the physiological mechanism is still unclear (Yanagawa et al 1999, Chang et al 2001, Kim et al 2003, Alfonso et al 2004, Lehtonen et al 2004, Xin et al 2005. Previous studies have reported that an increased level of PRDX1 might be involved in the protection of cancer cells against various therapeutic challenges ( Butzke et al 2004, Song et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the protein level, consistent with mRNA expression, MG132 , Immenschuh et al 2002, Wijayanti et al 2008, indicating the expression of PRDX1 is inducible by various stimuli. PRDX1 expression is also elevated in most cancers, although the physiological mechanism is still unclear (Yanagawa et al 1999, Chang et al 2001, Kim et al 2003, Alfonso et al 2004, Lehtonen et al 2004, Xin et al 2005. Previous studies have reported that an increased level of PRDX1 might be involved in the protection of cancer cells against various therapeutic challenges ( Butzke et al 2004, Song et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cells and mice lacking PRDX1 suggest that it not only regulates H 2 O 2 levels, but also possesses the properties of a tumor suppressor (Neumann et al 2003), which was further supported by the finding that PRDX1 interacts with c-Myc, thereby selectively inhibiting c-Myc transcriptional activity (Egler et al 2005). However, many studies indicated that aberrant increased expression of PRDX1 is found in various kinds of cancers including thyroid, lung, and breast (Yanagawa et al 1999, Chang et al 2001, Kim et al 2003, Alfonso et al 2004, Lehtonen et al 2004, Xin et al 2005, which obscures its actual role in tumorigenesis. As the hypoxic and unstable oxygenation microenvironment of a tumor is one of the key factors influencing tumor growth and progression, this increase in PRDX1 expression might be an adaptive response.…”
Section: Introductionmentioning
confidence: 96%
“…The disulfide bond is reduced back to the active thiol form (Cys-SH) by various mechanisms (2)(3)(4). We and others previously reported that Prx1 is frequently elevated in human lung cancer cells and tissues (5)(6)(7)(8)(9). Based on the observations in cultured cells and animals, a survival enhancing function of Prx1 has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic analysis, therefore, can play an important, non-redundant role in the identification and characterization of potential biomarkers and targets of cancer intervention. 19 Several studies have used advanced proteomics methods and statistical analyses to attempt to distinguish normal and cancer specimens for lung, 20 ovarian, 21 and breast cancer. 22 Based on our transcriptome results, we framed a similar hypothesis: nonmalignant proliferating B cells and malignant proliferating B cells will share the induction of important proliferation-associated proteins in comparison with non-proliferating controls; however, malignant cells will show additional changes in protein expression, including posttranslational modification, that are unique to their malignant state, over and above those changes associated with normal, mitogen-stimulated proliferation alone.…”
mentioning
confidence: 99%